Minimal Morse functions on a pair of manifolds - Prishlyak, O. O. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The existence theorem for a minimal Morse function on a pair of manifolds $(M_n,N_k)$, where $n - k ≥ 3,\; k ≥ 6$, is proved.